Method for treating wastewater containing fluoroquinolone antibiotics by using electrochemical membrane reactor

By using a titanium-based electrocatalytic film and a modified graphite felt as electrode film in an electrochemical membrane reactor, electrolyzing the fluoroquinolones-containing antibiotic wastewater, the problem of low degradation efficiency in the prior art was solved, and a 100% degradation rate was achieved.

CN119707044AActive Publication Date: 2025-03-28CHINA JAPAN FRIENDSHIP ENVIRONMENTAL PROTECTION CENT
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411998153.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade fluoroquinolones antibiotic wastewater, causing it to remain in the environment and cause health hazards.

Method used

An electrochemical membrane reactor was used to degrade antibiotics by using a titanium-based electrocatalytic film supported by an electrocatalyst and a modified graphite felt as a cathode film.

Benefits of technology

The specific surface area of ​​the anode film is increased by boron element doping, and the electrocatalytic activity is improved. The degradation rate reaches 100% in one hour of electrolysis. At the same time, the modified graphite felt produces more active substances, improving the degradation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226719910000051
    Figure BDA0005226719910000051
  • Figure BDA0005226719910000061
    Figure BDA0005226719910000061
Patent Text Reader

Abstract

The invention provides a method for treating wastewater containing fluoroquinolone antibiotics through an electrochemical membrane reactor, and belongs to the technical field of antibiotic wastewater treatment. According to the method, the wastewater containing the fluoroquinolone antibiotics is introduced into an electrochemical membrane reactor for electrolytic treatment, the electrochemical membrane reactor is provided with an anode membrane and a cathode membrane, and the anode membrane is a titanium-based electro-catalysis membrane loaded with an electro-catalyst. The specific surface area of the anode film can be effectively increased through doping of the boron element, the stability of the electrode film is improved, the electrocatalytic activity of the anode film is further improved, and the degradation rate reaches 100% after electrolysis is conducted for 1 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibiotic wastewater treatment, and in particular to a method for treating fluoroquinolone antibiotic wastewater using an electrochemical membrane reactor. Background Art

[0002] Fluoroquinolones are broad-spectrum antibiotics with strong antibacterial activity, no cross-resistance with other antibacterial drugs, and few toxic side effects. They are widely used in poultry, livestock, aquaculture and other breeding industries to prevent and treat animal diseases. Excessive use can lead to residues in animals, causing harm to human health. Fluoroquinolone antibiotics are highly soluble in water and are often detected in sewage treatment plants, rivers and groundwater. Because fluoroquinolone antibiotics have the characteristics of stable structure and high adsorption affinity, it is difficult to completely degrade them through traditional wastewater treatment technology.

[0003] At present, commonly used methods for treating antibiotics include physical methods, biological methods and chemical methods. Among them, physical methods mainly use adsorption and membrane separation methods to separate antibiotics from water bodies. Although the adsorption method has low cost and simple adsorbent preparation, the adsorbed antibiotics are easily desorbed under the influence of the outside world, causing secondary pollution to the environment. The membrane separation method has the advantages of simple operation, strong selectivity and low energy consumption, but it is prone to problems such as membrane pollution and secondary pollution of concentrated water, which seriously affects the interception of antibiotics. Electrochemical treatment of high-concentration fluoroquinolone antibiotic wastewater has low degradation efficiency: For example, Chinese patent CN109824214B discloses a device and method for treating wastewater containing fluoroquinolone antibiotics. High-concentration fluoroquinolone antibiotics are electrochemically electrolyzed, and the anode plate is titanium-based PbO 2 , the cathode plate is a stainless steel sheet, and the degradation rate of antibiotics can reach 98% in 4 hours. Therefore, it is of great significance to study a method for treating wastewater containing fluoroquinolone antibiotics with an electrochemical membrane reactor to improve the degradation efficiency. Summary of the invention

[0004] The object of the present invention is to provide a method for treating fluoroquinolone antibiotic wastewater by using an electrochemical membrane reactor, so as to solve the problem of low degradation efficiency of fluoroquinolone antibiotic wastewater.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for treating fluoroquinolone antibiotics wastewater with an electrochemical membrane reactor, comprising the following steps: passing the fluoroquinolone antibiotics wastewater into an electrochemical membrane reactor for electrolytic treatment; the electrochemical membrane reactor comprises an anode membrane and a cathode membrane, wherein the anode membrane is a titanium-based electrocatalytic membrane loaded with an electrocatalyst.

[0007] Preferably, the electrocatalyst loaded in the electrocatalyst-loaded titanium-based electrocatalytic membrane is boron-doped lead oxide.

[0008] Preferably, the method for preparing the titanium-based electrocatalyst membrane loaded with electrocatalysts is as follows: lead nitrate, boric acid and water are prepared into a mixed solution, and a titanium substrate is placed in the mixed solution for electrodeposition to obtain the titanium-based electrocatalyst membrane loaded with electrocatalysts.

[0009] Preferably, the cathode membrane of the electrochemical membrane reactor is modified graphite felt.

[0010] Preferably, the modified graphite felt is prepared by: immersing the graphite felt in a mixed dispersion, taking it out after the immersion is completed, drying it, and heat treating it to obtain the modified graphite felt.

[0011] Preferably, the mixed dispersion is made of carbon black, polytetrafluoroethylene emulsion and solvent.

[0012] Preferably, the electrolyte used in the electrolytic treatment is sodium sulfate, sodium chloride or sodium nitrate; the concentration of the electrolyte is 0.03-0.1 mol / L; and the pH value of the fluoroquinolone antibiotic-containing wastewater is 3.0-11.0.

[0013] Preferably, the distance between the anode membrane and the cathode membrane is 2 to 4 cm.

[0014] Preferably, the current density of the electrolysis is 10-20 mA / cm 2 .

[0015] Beneficial effects of the present invention:

[0016] (1) The present invention can effectively increase the specific surface area of ​​the anode film by doping with boron element, improve the stability of the electrode film, and further improve the electrocatalytic activity of the anode film. The degradation rate of antibiotics in wastewater after electrolysis for 1 hour reaches 100%.

[0017] (2) The modified graphite felt prepared by loading carbon black and polytetrafluoroethylene on graphite felt is used as a cathode membrane to generate more active substances, thereby improving the degradation efficiency of fluoroquinolone antibiotics. DETAILED DESCRIPTION

[0018] The present invention provides a method for treating fluoroquinolone antibiotics wastewater with an electrochemical membrane reactor, comprising the following steps: passing the fluoroquinolone antibiotics wastewater into an electrochemical membrane reactor for electrolytic treatment; the electrochemical membrane reactor comprises an anode membrane and a cathode membrane, wherein the anode membrane is a titanium-based electrocatalytic membrane loaded with an electrocatalyst.

[0019] In the present invention, the electrocatalyst loaded in the electrocatalyst-loaded titanium-based electrocatalytic membrane is boron-doped lead oxide.

[0020] In the present invention, the preparation method of the titanium-based electrocatalyst membrane loaded with electrocatalysts is as follows: lead nitrate, boric acid and water are prepared into a mixed solution, and a titanium substrate is placed in the mixed solution for electrodeposition to obtain the titanium-based electrocatalyst membrane loaded with electrocatalysts.

[0021] In the present invention, the molar ratio of lead nitrate to boric acid is 20-40:0.5-1.5; the deposition parameters are: deposition temperature is 30°C, current density is 1.5 mA / cm 2 , the deposition time is 1h.

[0022] In the present invention, the cathode membrane of the electrochemical membrane reactor is modified graphite felt.

[0023] In the present invention, the preparation method of the modified graphite felt is: immersing the graphite felt in the mixed dispersion liquid, taking it out after the immersion is completed, drying it, and heat treating it to obtain the modified graphite felt.

[0024] In the present invention, the mixed dispersion is made of carbon black, polytetrafluoroethylene emulsion and solvent.

[0025] In the present invention, in the mixed dispersion, the usage ratio of carbon black, polytetrafluoroethylene emulsion and solvent is 0.5-1.5g:1.0-2.5g:20-40mL; the mass fraction of the polytetrafluoroethylene emulsion is 60%.

[0026] In the present invention, the immersion time is 1 hour; the heat treatment temperature is 200-300° C., and the time is 0.5-1.5 hours.

[0027] In the present invention, the electrolyte used in the electrolytic treatment is sodium sulfate, sodium chloride or sodium nitrate; the concentration of the electrolyte is 0.03-0.1 mol / L; the pH value of the fluoroquinolone antibiotic-containing wastewater is 3.0-11.0, preferably 4.0-10.0, and more preferably 7.0.

[0028] In the present invention, the distance between the anode membrane and the cathode membrane is 2 to 4 cm, preferably 3 cm.

[0029] In the present invention, the current density of the electrolysis is 10-20 mA / cm 2 , preferably 12 to 18 mA / cm 2 , more preferably 15mA / cm 2 .

[0030] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0031] The titanium substrate and graphite felt used in the examples and comparative examples of the present invention are both pretreated titanium substrate and pretreated graphite felt.

[0032] In the present invention, the size of the titanium substrate is 50mm×30mm×2mm, and the pretreatment process of the titanium substrate is: the titanium plate is polished with 200#, 400#, 600#, 800# and 1000# sandpaper in sequence and rinsed with deionized water to obtain a titanium substrate with a smooth surface. Then the titanium substrate is immersed in an 80°C NaOH solution (concentration of 40wt%) for alkali washing for 2h to remove oil, and after degreasing, it is immersed in a slightly boiling oxalic acid solution (concentration of 10wt%) for reflux etching for 2h, and then taken out and rinsed with deionized water to obtain a titanium substrate with a pockmarked surface.

[0033] In the present invention, the size of the graphite felt is 50 mm×30 mm×2 mm, and the pretreatment process of the graphite felt is: the graphite felt is placed in pure water and acetone for ultrasonic treatment for 1 hour, and then dried at 100° C. for standby use.

[0034] Preparation Example 1

[0035] A mixed solution of lead nitrate and boric acid was prepared at a molar ratio of 30:0.5, with a concentration of 0.5 mol / L of lead nitrate. The pretreated titanium substrate was then placed in the mixed solution for electrodeposition at a temperature of 30°C and a current density of 1.5 mA / cm 2 , the deposition time is 1h, and a boron-doped lead oxide-titanium-based anode film is obtained, which is recorded as boron-doped lead oxide-titanium-based anode film-1.

[0036] Preparation Example 2

[0037] A mixed solution of lead nitrate and boric acid was prepared at a molar ratio of 30:1.0, and the concentration of lead nitrate was 0.5 mol / L. Then, the pretreated titanium substrate was placed in the mixed solution for electrodeposition, wherein the deposition temperature was 30°C and the current density was 1.5 mA / cm 2 , the deposition time is 1h, and a boron-doped lead oxide-titanium-based anode film is obtained, which is recorded as boron-doped lead oxide-titanium-based anode film-2.

[0038] Preparation Example 3

[0039] A mixed solution of lead nitrate and boric acid was prepared at a molar ratio of 30:1.5, with a concentration of 0.5 mol / L of lead nitrate. The pretreated titanium substrate was then placed in the mixed solution for electrodeposition at a temperature of 30°C and a current density of 1.5 mA / cm 2 , the deposition time is 1h, and a boron-doped lead oxide-titanium-based anode film is obtained, which is recorded as boron-doped lead oxide-titanium-based anode film-3.

[0040] Preparation Example 4

[0041] 0.5 g of carbon black and 1.5 g of polytetrafluoroethylene emulsion (mass fraction of 60%) were dispersed in a mixed solvent of deionized water and isopropanol (the volume of deionized water was 30 mL and the volume of isopropanol was 5 mL), and ultrasonically treated for 1 hour to obtain mixed dispersions with different carbon black contents. The pretreated graphite felt was immersed in the above mixed dispersions and ultrasonically treated for 1 hour. The mixture was taken out and placed in a constant temperature drying oven at 80°C for 12 hours. Finally, the mixture was placed in a muffle furnace and heat treated at 250°C for 1 hour to obtain a modified graphite felt cathode membrane, which was recorded as modified graphite felt cathode membrane-1.

[0042] Preparation Example 5

[0043] 1.0 g of carbon black and 1.5 g of polytetrafluoroethylene emulsion (mass fraction of 60%) were dispersed in a mixed solvent of deionized water and isopropanol (the volume of deionized water was 30 mL and the volume of isopropanol was 5 mL), and ultrasonically treated for 1 hour to obtain mixed dispersions with different carbon black contents. The pretreated graphite felt was immersed in the above mixed dispersions and ultrasonically treated for 1 hour. The mixture was taken out and placed in a constant temperature drying oven at 80°C for 12 hours. Finally, the mixture was placed in a muffle furnace and heat treated at 250°C for 1 hour to obtain a modified graphite felt cathode membrane, which was recorded as modified graphite felt cathode membrane-2.

[0044] Preparation Example 6

[0045] 1.5 g of carbon black and 1.5 g of polytetrafluoroethylene emulsion (mass fraction of 60%) were dispersed in a mixed solvent of deionized water and isopropanol (the volume of deionized water was 30 mL and the volume of isopropanol was 5 mL), and ultrasonically treated for 1 hour to obtain mixed dispersions with different carbon black contents. The pretreated graphite felt was immersed in the above mixed dispersions and ultrasonically treated for 1 hour. The mixture was taken out and placed in a constant temperature drying oven at 80°C for 12 hours. Finally, the mixture was placed in a muffle furnace and heat treated at 250°C for 1 hour to obtain a modified graphite felt cathode membrane, which was recorded as modified graphite felt cathode membrane-3.

[0046] The boron-doped lead oxide-titanium-based anode film prepared in Preparation Examples 1 to 3 and the modified graphite felt cathode film prepared in Preparation Examples 4 to 6 were used, a certain distance was set between the anode film and the cathode film, and they were placed in a plexiglass reactor (as an electrolytic cell), an external DC regulated power supply was connected, the positive electrode of the DC regulated power supply was connected to the anode film, and the negative electrode was connected to the cathode film, the plexiglass reactor was placed on a magnetic stirrer, and assembled into an electrochemical membrane reactor.

[0047] Application Example 1

[0048] The electrochemical membrane reactor assembled as above was used to electrolyze the wastewater containing fluoroquinolone antibiotics. The distance between the cathode membrane and the anode membrane was 2 cm. The initial concentration of antibiotics in the wastewater was 5 mg / L and the initial pH value was 7.0. The wastewater containing fluoroquinolone antibiotics and sodium sulfate were poured into the organic glass reactor so that the concentration of sodium sulfate electrolyte was 0.05 mol / L. The magnetic stirrer was turned on and the DC regulated power supply was started at the same time. The current density was adjusted to 20 mA / cm 2 The wastewater was electrolyzed, and the concentration of antibiotics in the wastewater was tested every 5 minutes during the electrolysis process. The test results are shown in Table 1.

[0049] Table 1 Degradation effect of different positive and negative electrode membranes on antibiotics

[0050]

[0051]

[0052] It can be seen from Table 1 that the degradation effect of antibiotics is different when the boron doping amount in the anode film is different. As the boron doping amount increases, the degradation effect can be significantly improved. The amount of carbon black added in the modified graphite felt cathode film also affects the degradation effect of antibiotics. The degradation effect is optimal when the amount of carbon black added is 1.0g.

[0053] Application Example 2

[0054] Boron-doped lead oxide-titanium-based anode film-3 and modified graphite felt cathode film-2 were used as anode film and cathode film to electrolyze wastewater containing fluoroquinolone antibiotics. The distance between the cathode film and the anode film was 3 cm. The initial concentrations of antibiotics in the wastewater were 10 mg / L, 20 mg / L, 30 mg / L, 50 mg / L, 100 mg / L, and 150 mg / L, respectively. The initial pH value was 7.0. The wastewater containing fluoroquinolone antibiotics and sodium sulfate were poured into a plexiglass reactor so that the concentration of sodium sulfate electrolyte was 0.05 mol / L. The magnetic stirrer was turned on, and the DC regulated power supply was started at the same time. The current density was adjusted to 20 mA / cm 2 The wastewater was electrolyzed, and the concentration of antibiotics in the wastewater was tested every 5 minutes during the electrolysis process. The test results are shown in Table 2.

[0055] Table 2 Degradation effect of antibiotics at different initial concentrations

[0056] Antibiotic concentration (mg / L) Degradation rate at 60 min (%) 10 100 20 100 30 100 50 100 100 98.2 150 96.5

[0057] It can be seen from Table 2 that, by using the electrochemical double membrane reactor of the present invention, the degradation rate is as high as 100% when the antibiotic concentration is lower than 50 mg / L after 60 minutes of electrolysis, and a good degradation effect can also be achieved for high-concentration antibiotic wastewater.

[0058] As can be seen from the above embodiments, the present invention provides a method for treating fluoroquinolone antibiotic wastewater by an electrochemical membrane reactor. The present invention passes fluoroquinolone antibiotic wastewater into an electrochemical membrane reactor for electrolytic treatment, wherein the electrochemical membrane reactor has an anode membrane and a cathode membrane, and the anode membrane is a titanium-based electrocatalytic membrane loaded with an electrocatalyst. The present invention can effectively increase the specific surface area of ​​the anode membrane by doping with boron elements, improve the stability of the electrode membrane, and further improve the electrocatalytic activity of the anode membrane, and the degradation rate of electrolysis for 1 hour reaches 100%.

[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for treating fluoroquinolone antibiotic wastewater using an electrochemical membrane reactor, characterized in that: The method comprises the following steps: passing fluoroquinolone antibiotic-containing wastewater into an electrochemical membrane reactor for electrolytic treatment; the electrochemical membrane reactor comprises an anode membrane and a cathode membrane, wherein the anode membrane is a titanium-based electrocatalytic membrane loaded with an electrocatalyst.

2. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 1, characterized in that: The electrocatalyst loaded in the electrocatalyst-loaded titanium-based electrocatalytic membrane is boron-doped lead oxide.

3. The method for treating fluoroquinolone antibiotic wastewater using an electrochemical membrane reactor according to claim 2, characterized in that: The preparation method of the titanium-based electrocatalyst membrane loaded with electrocatalysts comprises: preparing a mixed solution of lead nitrate, boric acid and water, placing a titanium substrate in the mixed solution for electrodeposition, and preparing the titanium-based electrocatalyst membrane loaded with electrocatalysts.

4. The method for treating fluoroquinolone antibiotics-containing wastewater by an electrochemical membrane reactor according to any one of claims 1 to 3, characterized in that: The cathode membrane of the electrochemical membrane reactor is modified graphite felt.

5. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 4, characterized in that: The preparation method of the modified graphite felt comprises: dipping the graphite felt in a mixed dispersion liquid, taking it out after dipping, drying it, and heat treating it to obtain the modified graphite felt.

6. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 5, characterized in that: The mixed dispersion is made of carbon black, polytetrafluoroethylene emulsion and solvent.

7. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 3, 5 or 6, characterized in that: The electrolyte used in the electrolytic treatment is sodium sulfate, sodium chloride or sodium nitrate; the concentration of the electrolyte is 0.03-0.1 mol / L; the pH value of the fluoroquinolone antibiotic-containing wastewater is 3.0-11.

0.

8. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 7, characterized in that: The distance between the anode membrane and the cathode membrane is 2 to 4 cm.

9. The method for treating fluoroquinolone antibiotics wastewater using an electrochemical membrane reactor according to claim 8, characterized in that: The current density of the electrolysis is 10-20 mA / cm 2 .

Citation Information

Patent Citations

  • Device and method for treating wastewater containing fluoroquinolone antibiotics

    CN109824214B

  • Nickel-boron-fluorine codoped lead dioxide positive pole and preparation method and application thereof

    CN107902731A

  • Device and method for treating wastewater containing fluoroquinolone antibiotics

    CN109824214A

  • Graphite felt cathode as well as preparation method and application thereof

    CN112076759A

  • Preparation method and application of cerium-doped lead dioxide electrode

    CN115613093A